2012
DOI: 10.1002/hep.25743
|View full text |Cite
|
Sign up to set email alerts
|

Vaniprevir with pegylated interferon alpha-2a and ribavirin in treatment-naïve patients with chronic hepatitis C: A randomized phase II study

Abstract: ; for the MK-7009 Protocol 007 Study GroupVaniprevir (MK-7009) is a macrocyclic hepatitis C virus (HCV) nonstructural protein 3/4A protease inhibitor. The aim of the present phase II study was to examine virologic response rates with vaniprevir in combination with pegylated interferon alpha-2a (Peg-IFN-a-2a) plus ribavirin (RBV). In this double-blind, placebo-controlled, dose-ranging study, treatment-naïve patients with HCV genotype 1 infection (n 5 94) were randomized to receive open-label Peg-IFN-a-2a (180 l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
41
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 24 publications
7
41
0
1
Order By: Relevance
“…The WT G1b replicon had EC 50 (ϮSD) values of 0.482 (Ϯ0.122) M and 0.269 (Ϯ0.096) M in the 48-h and 96-h assays, respectively, whereas the WT G1a replicon had an EC 50 (ϮSD) of Rarely observed in telaprevir studies G1b replicon (48-h assay) WT 0.482 Ϯ 0.122 0.961 (Ϯ0.132) M in the 96-h assay. The NS3 protease variants that were characterized included (i) variants most frequently observed (significantly enriched) in patients who did not achieve SVR in telaprevir-based regimens, including V36A/M, T54A/S, R155K/T, A156S/T, and V36MϩR155K (22); (ii) variants rarely observed (not significantly enriched) in patients who did not achieve SVR in telaprevir-based regimens, including V36C/G/I/L, I132V, V151A, R155G/I/M/S, A156F/N/V, V36AϩT54A, V36AϩR155K/T, V36LϩR155K, V36MϩR155T, V36A/MϩA156T, T54AϩA156S, T54SϩR155K, T54SϩA156S/T, R155TϩD168N, and V36Mϩ T54SϩR155K (22); and (iii) variants specifically observed for other HCV NS3 protease inhibitors, including Q41R, Q80R, and D168A/N/V, which are resistant to one or more macrocyclic inhibitors such as vaniprevir (36,44), ciluprevir (38), danoprevir (45), and simeprevir (46), and V55A, R109K, and V170A, which are resistant to linear NS3 protease inhibitors boceprevir (47,48) and SCH6 (49,50). The variants that were observed in clinical studies of telaprevir conferred different levels of resistance to telaprevir, with increases in EC 50 s ranging from 0.3-to Ͼ93-fold relative to the WT (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…The WT G1b replicon had EC 50 (ϮSD) values of 0.482 (Ϯ0.122) M and 0.269 (Ϯ0.096) M in the 48-h and 96-h assays, respectively, whereas the WT G1a replicon had an EC 50 (ϮSD) of Rarely observed in telaprevir studies G1b replicon (48-h assay) WT 0.482 Ϯ 0.122 0.961 (Ϯ0.132) M in the 96-h assay. The NS3 protease variants that were characterized included (i) variants most frequently observed (significantly enriched) in patients who did not achieve SVR in telaprevir-based regimens, including V36A/M, T54A/S, R155K/T, A156S/T, and V36MϩR155K (22); (ii) variants rarely observed (not significantly enriched) in patients who did not achieve SVR in telaprevir-based regimens, including V36C/G/I/L, I132V, V151A, R155G/I/M/S, A156F/N/V, V36AϩT54A, V36AϩR155K/T, V36LϩR155K, V36MϩR155T, V36A/MϩA156T, T54AϩA156S, T54SϩR155K, T54SϩA156S/T, R155TϩD168N, and V36Mϩ T54SϩR155K (22); and (iii) variants specifically observed for other HCV NS3 protease inhibitors, including Q41R, Q80R, and D168A/N/V, which are resistant to one or more macrocyclic inhibitors such as vaniprevir (36,44), ciluprevir (38), danoprevir (45), and simeprevir (46), and V55A, R109K, and V170A, which are resistant to linear NS3 protease inhibitors boceprevir (47,48) and SCH6 (49,50). The variants that were observed in clinical studies of telaprevir conferred different levels of resistance to telaprevir, with increases in EC 50 s ranging from 0.3-to Ͼ93-fold relative to the WT (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…These results are in agreement with other previous in vitro resistance studies and clinical observations. For example, R155 in GT 1a virus and D168 in GT 1b virus, conferring cross-resistance to other macrocyclic PIs, are also commonly seen in patients treated with vaniprevir, danoprevir, BI 201335, and TMC-435 (7,12,15,26). Clinical studies with telaprevir identified V36A/M, T54A, R155T/K, and A156S/V/T mutations in NS3.…”
Section: Discussionmentioning
confidence: 99%
“…NS3/4A HCV PIs achieve high antiviral potency by blocking HCV poly-protein cleavage and may also neutralize HCV NS3 protease-mediated interference with the innate immune system. Through this mechanism, HCV NS3/4A PIs reverse the HCV NS3 protein's capacity to block intracellular signal-transduction pathways for endogenous IFN production in vitro and may also do so in vivo [19].…”
Section: Host Factorsmentioning
confidence: 99%